Coresistance to Neomycin and Kanamycin by Mutations in an Escherichia coli Locus that Affects Ribosomes - Apirion, D. (1968)
Mutant strains resistant to neomycin or to kanamycin sulfate were isolated from Escherichia coli K-12. Nine mutants were analyzed; all were resistant to both antibiotics (about 150 and 100 μg/ml, respectively), and were designated nek. In the mutant strains, the ribosomes are changed from those of the parental strain; for when they were used in assays for polypeptide formation directed by polyadenylic acid or polycytidylic acid, coding fidelity in presence of the drugs was increased and inhibition of synthesis by the drugs was lessened. Mating experiments and transduction tests showed that all of the nine nek mutants are either closely linked or allelic, and the nek locus is closely linked to two genes—str (streptomycin) and spc (spectinomycin)—known to affect the 30S ribosome. The two nek mutants tested were recessive to the sensitive, wild-type allele. When the nek mutants were compared to the parental strain, pleiotropic effects of the nek mutations were observed. Resistance to low levels of streptomycin and spectinomycin was increased, whereas resistance to chloramphenicol was decreased. Also, the mutants were less able to adapt to high concentrations of lincomycin, and could no longer show phenotypic suppression of an arginine requirement by neomycin or kanamycin. Such pleiotropic effects are suggested to be the rule for mutations in genes that participate in the biosynthesis of a cellular organelle.